AMMSA-21: a revised version of the Acceptance of Modern Myths About Sexual Aggression Scale in English, German, Polish and Spanish (AMMSA-21: una versión revisada de la escala Aceptación de Mitos Modernos sobre la Agresión Sexual en inglés, alemán, polaco y español). Issue 3 (2nd September 2022) - Bohner, Gerd; Weiss, Alexa; Schirch, Cindy; Zöllner, Lea; Lipińska, Aldona; Sempere, María-José; Megías, Jesús L.
ABSTRACT: The authors present a revised version of the Acceptance of Modern Myths About Sexual Aggression scale (AMMSA-21) in four languages (English, German, Polish and Spanish) and examine its reliability and validity (total N = 1, 459). AMMSA-21 addresses themes emerging in recent public discourse (e.g., beliefs about false accusations) and contents similar to the original scale (e.g., antagonism towards victims' demands); with 21 items, it is 30% shorter than the original. Factor analyses suggested that AMMSA-21 may be treated as a unidimensional construct. Across the four language versions, AMMSA-21 showed high internal consistency and criterion validity (positive correlations with hostile and benevolent sexism, social dominance orientation, right-wing authoritarianism); its scores were unrelated to socially desirable responding. Also, AMMSA-21 predicted judgements of victim-blaming and rape proclivity in relation to acquaintance-rape scenarios. Mean differences across language versions (Spanish < English = German < Polish) are discussed in terms of cultural influences. In sum, AMMSA-21 represents a reliable, valid and economical measure of contemporary sexual aggression myths.